Fluorinated polymer membranes as advanced substrates for portable analytical systems and their proof of concept for colorimetric bioassays - Brito-Pereira, R. (2021)
Portable analytical systems are increasingly required for clinical analysis or environmental monitoring, among others, being materials with tailored physicochemical properties among the main needs for successful functional implementation. This article describes the processing of fluorinated poly(vinylidene-co-trifluorethylene), P(VDF-TrFE), membranes with tailored morphological and physicochemical properties to be used as microfluidic substrates for portable analytical systems, commonly called point-of-care systems in the medical field. The morphology of the developed membranes includes spherulitic, porous, randomly oriented, and oriented fibers. Furthermore, the processed hydrophobic P(VDF-TrFE) membranes were post-treated by oxygen plasma to make them superhydrophilic. The influence of morphology and plasma treatment on the physicochemical properties and capillary flow rates was evaluated. Microfluidic systems were then designed and printed by wax printing for the colorimetric quantification of glucose. The systems comprise eight reaction chambers, each glucose concentration (25, 50, 75, and 100 mg dL–1) being measured in two reaction chambers separately and at the same time. The results demonstrate the suitability of the developed microfluidic substrates based on their tailorable morphology, improved capillary flow rate, wax print quality, homogeneous generation of colorimetric reaction, and excellent mechanical properties. Finally, the possibility of being reused, along with their electroactive properties, can lead to a new generation of microfluidic substrates based on fluorinated membranes.